Design of DC to 40 GHz GaAs-based MMIC Attenuators by Utilizing Full-chip Numerical Analyses - Bayrak, Mehmet Emin; Tekin, Harun; Savci, Huseyin Serif (Applied Computational Electromagnetics Society Journal (ACES), 2024)
In this study, a numerical analysis-based design methodology of monolithic microwave integrated circuit (MMIC) attenuators on a GaAs-based microwave integrated passive device (IPD) technology is presented. The designs have 0 dB, 3 dB, 4 dB, 6 dB, 10 dB, 12 dB, 20 dB, and 30 dB attenuation from DC to 40 GHz. The attenuators are designed for a maximum RF power of 26 dBm and a maximum die area of 0.25 mm2. The circuits are physically compact but electrically large. The finite element method and Method of Moments (MoM)-based analyses are used. The MoM-based solutions show close correlations with the measurements. The measured return losses are better than 20 dB, and insertion loss variation is less than 0.5 dB across the entire band. This paper explains the detailed design steps and numerical electromagnetic setup to achieve first-pass success.